Novel Methods to Preserve Mesenchymal Stem Cells at low Temperatures - Lakey, Jonathan (2024)
In recent years, stem cell therapy has been applied to the treatment of many diseases. Stem cells are extensively researched fortheir potential to replace diseased tissues in conditions such as degenerative diseases, tumors, trauma, and others, collectively knownas regenerative therapy. However, as age advances, the number and quality of stem cells decreases; by the age of 50, a person has lessthan 3% of the stem cells they had at birth. Although stem cells can be preserved in vitro for long periods of time, their activity aftercryopreservation and recovery does not reach the level expected under current technological conditions. Therefore, it is particularlyimportant to find a more suitable freezing method. In this paper, we present a novel method for freezing stem cells that ensures highcellular activity after recovery. In this study we validate a combinational approach of using two permeating cryoprotective agents, atlower than normal concentrations resulting in higher recovery post cryopreservation of human mesenchymal stem cells.